WELCOMING LGBT RESIDENTS a practical guide for senior living staff. - Johnston, Tim R. ([S.l.] : ROUTLEDGE, 2019)
Welcoming LGBT Residents is the first comprehensive guide to working with LGBT older adults in senior living settings. The LGBT older adult population represents one of the fastest-growing subpopulations within our aging society. Despite the increasing demand for LGBT-affirming services there is an absence of training books for care providers. This dual-purpose text is appropriate for training and as a guide to answer questions that may come up during daily tasks. It is based on the most recent research and includes stories and testimonials from LGBT older adults and providers in the field. Chapters include: LGBT-inclusive intake and conversations; Gender identity and expression; Memory care and LGBT people; Navigating family dynamics; Addressing conflict between residents; Staff opinions, beliefs, and training. This timely book will be of interest to professional care providers, from long-term care nurses and assisted living administrators to staff in retirement communities, as well as students in gerontology, health care administration, and social work courses.
OCLC-licensed vendor bibliographic record.
Keywords: Older gays -- Care; Older people -- Housing; MEDICAL / Health Care Delivery